Comparing two different option pricing methods - Alessandro Bondi; Dragana Radojicić; Thorsten Rheinländer (Risks, 2020)
Motivated by new financial markets where there is no canonical choice of a risk-neutral measure, we compared two different methods for pricing options: calibration with an entropic penalty term and valuation by the Esscher measure. The main aim of this paper is to contrast the outcomes of those two methods with real-traded call option prices in a liquid market like NASDAQ stock exchange, using data referring to the period 2019-2020. Although the Esscher measure method slightly underperforms the calibration method in terms of absolute values of the percentage difference between real and model prices, it could be the only feasible choice if there are not many liquidly traded derivatives in the market.
Keywords: 330; geometric Esscher measure; calibration with entropic penalty term; financial markets; option pricing